Lichens Diversity in State University of Malang and Prospects as a Source of Learning Thallophyte Botany - Mahanal, Susriyati (Proceeding International Conference on Global Resource Conservation, 2013)
Lichen is a thallophyte consists of fungus (mycobiont) and alga (photobiont) in a symbiotic relationship. Lichen can grow in a variety of habitats such as trees, on the ground, even in the rock surface. As one of the subjects in the course of thallophyte botany, during this lichen was observed by the students of botanycal labolatory specimen collections that have been preserved. In fact, around on the State University of Malang Collage lichens are found growing in various habitats. Thus, the area of Malang State University Collage can be used as a natural laboratory to improve studentâs knowledge about the several of lichen. The study was conducted in June - July 2012 in the area of Malang State University collage area of 453 860 m2. The purpose of research is to determine the diversity of lichens in the area of Malang State University collage and its prospects as a learning resource thallophyte botany subjects. This research is a descriptive exploratory. The method which has been used is modification of Nimisâs method. Lichen diversity studies based on morphological, anatomical and chemical characters. In this research found 10 species of lichen, Acrocordia salweyi, Graphis scripta, Graphis elegans, Pannoparmelia sp., Parmelinopsis subfatiscens, Parmotrema eurysacum (Hue.) Hale, Xanthoparmelia tegeta Elix, Xanthoparmelia xanthofarinosa Elix. Peltigera sp, Physcia aipolia. Based on that result, it was known that lichen diversity in State University of Malang had prospect to be applied as learning resourcesof thallophyte botany subject. Â Keywords: lichen diversity, thallophyte botany